2006
DOI: 10.1186/1471-2334-6-13
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-linked immunoassay for dengue virus IgM and IgG antibodies in serum and filter paper blood

Abstract: BackgroundThe reproducibilty of dengue IgM and IgG ELISA was studied in serum and filter paper blood spots from Vietnamese febrile patients.Methods781 pairs of acute (t0) and convalescent sera, obtained after three weeks (t3) and 161 corresponding pairs of filter paper blood spots were tested with ELISA for dengue IgG and IgM. 74 serum pairs were tested again in another laboratory with similar methods, after a mean of 252 days.ResultsCases were classified as no dengue (10 %), past dengue (55%) acute primary (7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 21 publications
1
36
0
Order By: Relevance
“…The pattern of seroconversion seen among a select population of children attending the medical facility for gastrointestinal symptoms in the Dominican Republic [12] and among febrile persons who were screened for dengue in Jamaica [14] was similar to the pattern seen in this study. Interestingly, the pattern of IgG seroprevalence seen in our study was also similar to the patterns of high IgG seroprevalence that were reported in population-based prospective studies from some of the other highly endemic countries in the Americas [11,[22][23][24][25] and those of other highly endemic countries in southeast Asia [26][27][28].…”
Section: Discussionsupporting
confidence: 88%
“…The pattern of seroconversion seen among a select population of children attending the medical facility for gastrointestinal symptoms in the Dominican Republic [12] and among febrile persons who were screened for dengue in Jamaica [14] was similar to the pattern seen in this study. Interestingly, the pattern of IgG seroprevalence seen in our study was also similar to the patterns of high IgG seroprevalence that were reported in population-based prospective studies from some of the other highly endemic countries in the Americas [11,[22][23][24][25] and those of other highly endemic countries in southeast Asia [26][27][28].…”
Section: Discussionsupporting
confidence: 88%
“…This is important because filter-paper blood spots are easier to obtain than venous blood in infants and young children. Although filter-paper specimens have been used for detecting anti-DENV IgM, 22,23 no reports describe measurement of anti-DENV IgA in this sample type. Even though the sensitivity of anti-DENV IgM detection in saliva was lower than that of IgM and IgA in serum and filter-paper blood spots, it could potentially be useful for epidemiological surveillance and in confirmation of dengue in an outbreak situation in a particular community.…”
Section: Discussionmentioning
confidence: 98%
“…There was no difference in the storage length between the study groups. However, even the long storage period does not have any remarkable effect on the IgG antibody (53) or hsCRP levels (54).…”
Section: Discussionmentioning
confidence: 99%